PERBANDINGAN STRATEGI PEMBELAJARAN TIPE STAD (STUDENT TEAMS ACHIEVEMENT) DAN STRATEGI PEMBELAJARAN TIPE TGT (TEAM-GAMES-TOURNAMENT) TERHADAP HASIL BELAJAR PKn MATERI POKOK DEMOKRASI PANCASILA DI KELAS X SMA NEGERI 1 BATANGONANG - RISWANDI HARAHAP (Jurnal Education and Development, 2018)
The study aims to look at the difference between the Comparison Results Learning Civics Topic Pancasila Democracy Kooperatife Learning Model Using Type STAD With Learning Model Kooperatipe TGT Type Class X SMA Negeri 1 Batangonang. The population number of 258 people. Sample of 64 people. The collected data were analyzed with descriptive analysis used t-test test The research study Pancasila democracy Civics subject matter using type STAD cooperative learning model has an average value of 57.59 in the category of "Less". While studying Civics subject matter Pancasila democracy using cooperative learning model type TGT has an average value of 59.34 in the category of "Less". Based on the calculations performed to test the hypothesis that the price obtained TTable upheld the 95% significance level with df = 62 is 1.667. If prices were at 0.75 thitung compared with 1.667 for the TTable thitung smaller than TTable or 0.75 <1.667 which means that the alternative hypothesis is rejected truth. This means that the alternative hypothesis is rejected. Instead the null hypothesis is accepted. That is, there was no significant difference between the learning outcomes of Pancasila democracy Civics subject matter using cooperative learning model type STAD and TGT cooperative learning model type Class X student of SMA Negeri 1 Batangonang